An indication of the existence of a solar wind strahl at 10 AU. Issue 11 (6th June 2013) - Walsh, A. P.; Arridge, C. S.; Masters, A.; Lewis, G. R.; Fazakerley, A. N.; Jones, G. H.; Owen, C. J.; Coates, A. J.
<x xml:space="preserve">Abstract</x> [1] The solar wind electron distribution is observed near and within 1 AU to consist of three components: a thermal core, a suprathermal halo, and a suprathermal strahl. The former two components are isotropic, while the strahl is field aligned and flows outward along the interplanetary magnetic field. The evolution of solar wind electrons with heliocentric distance is poorly understood; although the halo is thought to be formed through pitch angle (PA) scattering of the strahl, the responsible physical process has not been conclusively identified. Measurements of solar wind electrons throughout the heliosphere are required to solve this problem. We present the first observations of the suprathermal components of the solar wind electron distribution made outside 5 AU. We find indications of a strahl component narrower than that predicted by extrapolating observations and models of electrons in the inner heliosphere, suggesting the rate of electron pitch angle scattering in the solar wind can decrease with increasing heliocentric distance.